1989
DOI: 10.1128/jvi.63.3.1302-1309.1989
|View full text |Cite
|
Sign up to set email alerts
|

Determinants in the 5' noncoding region of poliovirus Sabin 1 RNA that influence the attenuation phenotype

Abstract: A number of recombinants between the virulent Mahoney and attenuated Sabin strains of type 1 poliovirus were constructed by using infectious cDNA clones of the two strains. To identify a strong neurovirulence determinant(s) residing in the genome region upstream of nucleotide position 1122, these recombinant viruses were subjected to biological tests, including monkey neurovirulence tests. The results of the monkey neurovirulence tests suggested the important contribution of an adenine residue (Mahoney type) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(118 citation statements)
references
References 21 publications
7
109
0
2
Order By: Relevance
“…In the guts of vaccinees, such reversions occur very often and quite rapidly at positions 480, 481, and 472 in the RNAs of OPV serotypes 1, 2, and 3, respectively (307-311; reviewed in references 312 to 314), leading to restoration of their somewhat impaired secondary (for serotypes 1 and 3) or tertiary (for serotype 2) structures (104, 311, 315) ( Fig. 4) and, consequently, translational activity (316)(317)(318)(319) and neurovirulence (308,315,320,321).…”
Section: Rehabilitation After Adverse Changes In the Untranslated Regmentioning
confidence: 99%
“…In the guts of vaccinees, such reversions occur very often and quite rapidly at positions 480, 481, and 472 in the RNAs of OPV serotypes 1, 2, and 3, respectively (307-311; reviewed in references 312 to 314), leading to restoration of their somewhat impaired secondary (for serotypes 1 and 3) or tertiary (for serotype 2) structures (104, 311, 315) ( Fig. 4) and, consequently, translational activity (316)(317)(318)(319) and neurovirulence (308,315,320,321).…”
Section: Rehabilitation After Adverse Changes In the Untranslated Regmentioning
confidence: 99%
“…Numerous studies show potential attenuating mutations for each serotype of OPV virus based on: (1) sequence comparisons between OPV virus strains and parental WPVs, (75,76) (2) sequence comparisons and/or neurovirulence testing in monkeys or mice of recombinant virus strains (i.e., swapping genetic segments between attenuated and neurovirulent strains) and/or site-directed mutants, (47,50,(77)(78)(79)(80)(81)(82)(83)(84) (3) OPV-related virus mutant strains after exposure to high temperature, (85) (4) OPV-related virus strains excreted by immunocompetent vaccine recipients without VAPP, (48,(86)(87)(88)(89) (5) OPV-related virus strains isolated from VAPP cases, (44)(45)(46)48,(90)(91)(92)(93)(94)(95)(96)(97)(98)(99) (6) strains isolated during cVDPV outbreaks, (15,57,100,101) (7) strains excreted by immunodeficient VDPV excretors, (102-106) (8) strains obtained during sequential passages after OPV administration in humans, (107) (9) strains obtained during sequential passages of OPV-related viruses in monkey tissues, (108) and (10) strains obtained from passages in cell culture. …”
Section: Attenuation and Reversionmentioning
confidence: 99%
“…(77,81,82,97,111) Several studies show that some of the attenuating mutations of OPV1 revert in primary vaccine recipients over the period of excretion, although reversion at nt position 480, which can occur by direct reversion or by a compensating substitution at nt position 525, varies with respect to the proportion of primary vaccine recipients and time in different studies. (18,79,112) The virus strains isolated from type 1 VAPP cases also show the reversion of several attenuating mutations, most notably at nt position 480. (48,51,86,88,89,91,(93)(94)(95)(96)(97) One study in transgenic mice with uncertain extrapolation to humans showed that the PD 50 values range from 4.5 to 5.8 for VAPP viruses, which suggests greater neurovirulence than OPV1 (PD 50 around 8.0) and lower neurovirulence than the lab-adapted WPV1 Mahoney strain (PD 50 around < 2.3).…”
Section: Opv1mentioning
confidence: 99%
“…Studies on the accumulation of revertants during cultivation of the Sabin strains in different cell substrates at various levels of confluence showed that the rate of revertant selection varied significantly and seemed t o be dependent on cellular factors. Mutations a t other sites of the same F-domain of the 5'-untranslated region were implicated in attenuation of OPV of types 1 and 2 [Christodoulou et al, 1990;Kawamura et al, 1989;Macadam et al, 1991a,b;Moss et al, 1989;Ren et al, 19911. In this communication we demonstrate that G +A reversion at position 480 of Sabin type 1, and A + G reversion at position 481 of Sabin type 2, also accumulate during virus passaging in vitro and therefore reversion in the F-domain of the poliovirus 5'-untranslated region is a common phenomenon for all three Sabin serotypes. The results obtained in this netic stability described in this paper may be useful for the improvement of vaccine manufacturing consistency and evaluation of the stability of prospective vaccine strains.…”
Section: Introductionmentioning
confidence: 99%